SISTEM PENYAMPAIAN INOVASI MENDUKUNG PERCEPATAN HILIRISASI DAN ADOPSI TEKNOLOGI INTRODUKSI PERTANIAN / Innovation Delivery System to Support the Downstream Acceleration and the Adoption of Agricultural Introduction Technology - Rahmi Wahyuni (Badan Penelitian dan Pengembangan Pertanian, 2021)
Many technology innovations have been disseminated by agricultural research and study institutions, but have not been utilized or have not been continuously adopted by farmers so that they have not been able to significantly boost the economy of agricultural communities. This is partly due to gaps in the delivery of innovation (delivery system) and innovation acceptance (receiving system). This paper aims to identify the process of delivering innovation to support speeding up of adoption and downstreaming of introduce inovation technology application, as recommendations in preparing dissemination strategy effective agricultural technology that could be implemented in a sustainable way by farmers. In speeding up of adoption and downstreaming of introduce inovation technology application, extension workers are the spearhead in the dissemination of agricultural technology innovations. So far, counseling has focused too much on the delivery of program activities such as input supply and technical services so as to ignore farmers (farmer empowerment) and extension workers (competence or credibility extension workers) that should need to be improved.The essence of a counseling is empowering farmers. Associated with the credibility of an agricultural instructor must have competence, 1) threshold competencies, namely the main characteristics that must be owned by an instructor such as basic knowledge and expertise, and 2) differentiating competencies, are the distinguishing factors between one instructor with another high-performing with the other low performance. So as to create counseling that functions as a motivator, dynamic, facilitator and consultant for farmers.Keywords: Agricultural, innovation, extension, adoption AbstrakBanyak inovasi teknologi yang sudah terdiseminasikan oleh lembaga penelitian dan pengkajian pertanian, tetapi tidak termanfaatkan atau belum diadopsi oleh petani secara berkesinambungan sehingga tidak mampu mendongkrak perekonomian masyarakat pertanian secara signifikan. Hal ini antara lain disebabkan oleh kesenjangan dalam penyampaian inovasi (delivery system) dengan penerimaan inovasi (receiving system). Tulisan ini mengidentifikasi proses penyampaian inovasi dalam mendukung upaya percepatan adopsi dan hilirisasi penerapan teknologi introduksi, sebagai rekomendasi dalam menyusun strategi diseminasi teknologi pertanian yang efektif agar dapat diimplementasikan secara berkelanjutan oleh petani. Dalam percepatan adopsi dan hilirisasi teknologi menjadikan penyuluh sebagai ujung tombak diseminasi inovasi pertanian. Selama ini penyuluhan lebih fokus pada penyampaian program kegiatan seperti suplai input dan layanan teknis sehingga mengabaikan pemberdayaan petani dan penyuluh (kompentensi atau kredibilitas) yang seharusnya perlu ditingkatkan. Esensi penyuluhan pada prinsipnya adalah pemberdayaan petani. Terkait dengan kredibilitas, penyuluh pertanian harus mempunyai kompetensi: 1) threshold competencies, yaitu karakteristik utama yang wajib dimiliki seperti pengetahuan dan keahlian dasar, dan 2) differentiating competencies, faktor pembeda antara penyuluh yang memiliki kinerja tinggi dengan kinerja rendah, sehingga penyuluh mampu berfungsi sebagai motivator, dinamisator, fasilitator, dan konsultan bagi petani.Kata kunci: Pertanian, inovasi, penyuluhan, adopsi